Cross-linked polyvinyl chloride resin
Patent Information
- Application Number
- JP2025057814
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0012】 本発明の架橋塩化ビニル系樹脂は、その成型加工品において、高い艶消し性を有し、且つ引張強度や引張り伸び性などの機械的強度にも高度に優れるものになり、大変有用である。
Smart Images

Figure 2026165433000001 
Figure 2026165433000002 
Figure 2026165433000003
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to a crosslinked vinyl chloride-based resin, specifically, to a crosslinked vinyl chloride-based resin obtained by copolymerizing a vinyl chloride-based monomer component containing vinyl chloride as a main component and a crosslinkable monomer component composed of a vinyl compound copolymerizable therewith.
BACKGROUND ART
[0002] As a resin material having flame retardancy and the like and further excellent in molding processability, a vinyl chloride-based resin for paste processing (hereinafter sometimes simply abbreviated as "paste vinyl chloride") is known. Such paste vinyl chloride is generally produced by emulsion polymerization of a vinyl chloride-based monomer component containing vinyl chloride as a main component. The obtained paste vinyl chloride is kneaded with a plasticizer, a filler, a stabilizer or other compounding agents to prepare a sol, and the sol is used for various molding processes. For example, it is usefully used in applications such as wall materials, floor materials, automobile interior parts, electric wires, and daily miscellaneous goods.
[0003] In recent years, for the molded articles using the above paste vinyl chloride, as a consumer preference, so-called good matting properties, which have low surface gloss, anti-glare properties, a dry feel, and a calm appearance, are often required. As a method for enhancing the matting property of a molded article of paste vinyl chloride, in the method for producing the paste vinyl chloride, a method of allowing the emulsion polymerization of the vinyl chloride-based monomer component to proceed in the presence of a crosslinking agent is effective (for example, Patent Document 1).
[0004] That is, in the crosslinked vinyl chloride-based resin obtained by emulsion polymerization in the presence of the crosslinking agent, a fine gel content insoluble in tetrahydrofuran (THF) (hereinafter sometimes simply abbreviated as "gel content") is dispersed in the main resin phase of a linear polymer soluble in THF due to crosslinking. In the molded product thereof, the fine gel content is exposed on the surface to form a surface state where light is diffusely reflected, and as a result, the excellent matting effect is exhibited. Further, when molded into a sheet form, the anti-blocking property and the like of the molded product are also improved.
[0005] Thus, in the emulsion polymerization of vinyl chloride monomer components in the presence of such crosslinking agents, it is possible to use not only one type of crosslinking agent alone, but also two or more types in combination. Furthermore, when using two or more types in this way, there are known methods of using a crosslinking agent with a high monomer reactivity ratio relative to vinyl chloride and a crosslinking agent with a low monomer reactivity ratio (Patent Document 2), and more specifically, a method of using allyl methacrylate, which belongs to the former type of crosslinking agent with a high monomer reactivity ratio relative to vinyl chloride, and triallyl cyanurate, which belongs to the latter type of crosslinking agent with a low monomer reactivity ratio (Patent Document 3). [Prior art documents] [Patent Documents]
[0006] [Patent Document 1] Special Publication No. 63-058858 [Patent Document 2] Japanese Patent Application Publication No. 61-293203 [Patent Document 3] Japanese Patent Publication No. 2009-179744 [Overview of the Initiative] [Problems that the invention aims to solve]
[0007] As described above, the method of obtaining a crosslinked vinyl chloride resin by emulsion polymerization of vinyl chloride monomer components in the presence of a crosslinking agent makes it possible to impart a high matte finish to the molded product. In Patent Document 1, as a specific embodiment, the gel content is required to be 5 to 80% by mass, while the average degree of polymerization of the THF soluble phase is generally 800 or higher, preferably 1100 or higher.
[0008] However, cross-linked polyvinyl chloride resins of this type are not quite sufficient in terms of mechanical strength, such as tensile strength and tensile elongation. This has made them unsuitable for many molding applications of paste PVC where high mechanical strength is required. In particular, flooring materials require high resistance to the loads of people, placed objects, and falling objects, and improvement was strongly desired.
[0009] Therefore, a major challenge was the development of a cross-linked polyvinyl chloride resin that possesses both high matte finish and excellent mechanical strength. [Means for solving the problem]
[0010] In view of the above-mentioned problems, the inventors have diligently continued their research. As a result, they have found that in cross-linked vinyl chloride resins, when both a) the gel content (gel content) and b) the average degree of polymerization of the THF-soluble phase are high to specific values, both high matteness and high mechanical strength are achieved, leading to the completion of the present invention.
[0011] That is, a vinyl chloride monomer component mainly containing vinyl chloride and a crosslinkable monomer component consisting of a vinyl compound that can copolymerize with it are copolymerized. a) The gel content is greater than 80% by mass and less than or equal to 90% by mass, b) The average degree of polymerization of the THF-soluble phase is between 1000 and 4500. This is a crosslinked vinyl chloride resin characterized by the following: [Effects of the Invention]
[0012] The cross-linked vinyl chloride resin of the present invention is extremely useful because, in molded products it exhibits high matte finish and also possesses excellent mechanical strength, such as tensile strength and tensile elongation. [Modes for carrying out the invention]
[0013] Embodiments of the present invention will be described below. However, the present invention is not limited to these embodiments. In this specification, unless otherwise specified, the notation "A~B" for numerical values A and B means "A or greater and B or less". If a unit is attached only to numerical value B in such notation, that unit shall also apply to numerical value A. In addition, the words "or" and "or else" mean logical OR unless otherwise specified. In addition, the notation "E1 and / or E2" for elements E1 and E2 means "E1 or E2, or a combination thereof".
[0014] In this embodiment, the crosslinked vinyl chloride resin is obtained by copolymerizing a vinyl chloride monomer component mainly containing vinyl chloride with a crosslinkable monomer component consisting of a vinyl compound that can copolymerize with the same.
[0015] Here, in the above vinyl chloride monomer component, "primarily vinyl chloride" means that not only is vinyl chloride used alone as the monomer, but vinyl chloride may also be used as the main component, mixed with monomers that can copolymerize with vinyl chloride. For example, in the embodiment in which monomers copolymerizable with vinyl chloride are used in mixture, vinyl chloride should be 50% by mass or more of the total, and preferably 70% by mass or more.
[0016] Examples of monomers copolymerizable with vinyl chloride include olefin compounds such as ethylene and propylene; vinyl esters such as vinyl acetate and vinyl propionate; unsaturated monocarboxylic acids such as acrylic acid and methacrylic acid; unsaturated monocarboxylic acid esters such as methyl acrylate, ethyl acrylate, n-butyl acrylate, 2-hydroxyethyl acrylate, methyl methacrylate, ethyl methacrylate, and N,N-dimethylaminoethyl methacrylate; unsaturated amides such as acrylamide and methacrylamide; unsaturated nitriles such as acrylonitrile and methacrylonitrile; unsaturated dicarboxylic acids such as maleic acid and fumaric acid; esters and anhydrides thereof; N-substituted maleimides; vinyl ethers such as vinyl methyl ether and vinyl ethyl ether; and vinylidene compounds such as vinylidene chloride.
[0017] In the present embodiment, the vinyl chloride-based monomer component is copolymerized with a crosslinkable monomer component composed of a vinyl compound copolymerizable therewith to form a crosslinked vinyl chloride-based resin. Here, the crosslinkable monomer component composed of a vinyl compound copolymerizable with the vinyl chloride-based monomer component is a polyfunctional compound so-called a crosslinking agent, and details thereof will be described later in the section of emulsion polymerization for obtaining the crosslinked vinyl chloride-based resin.
[0018] Among the crosslinked vinyl chloride-based resins obtained by copolymerizing the vinyl chloride-based monomer component and the crosslinkable monomer component as described above, the one of the present embodiment has a) a gel content of more than 80 mass% and 90 mass% or less, which is high, and b) an average degree of polymerization of the THF-soluble phase portion of 1000 or more and 4500 or less, which is also high Exhibits unique properties.
[0019] Since both a) the gel content and b) the average degree of polymerization of the THF-soluble phase portion are thus high at specific values, the crosslinked vinyl chloride-based resin of the present embodiment has high matting properties in its molded product and is also highly excellent in mechanical strength such as tensile strength and tensile elongation.
[0020] Here, a) the gel content of the crosslinked vinyl chloride resin is important for enhancing the mechanical strength of the molded product and further improving the matting property. The value is more preferably 82% by mass or more and 88% by mass or less. When a) the gel content is 80% by mass or less as described above, neither the mechanical strength nor the matting property of the molded product is sufficient. On the other hand, when a) the gel content exceeds 90% by mass as described above, the molding processability is poor and the strength is remarkably reduced.
[0021] Further, b) the average polymerization degree of the THF-soluble phase portion of the crosslinked vinyl chloride resin has the effect of further increasing the high mechanical strength provided by the high a) gel content, to a level that allows satisfactory use even in molded product applications that require particularly high such properties, such as flooring materials. As can be understood from the description in Patent Document 1 that regarding crosslinked vinyl chloride resins, "when the fine gel fraction insoluble in THF exceeds 80% by mass, the average polymerization degree of the THF-soluble portion decreases too much, which is not preferable" (lines 15 to 18 of Column 5), usually, in the crosslinked vinyl chloride resin in which a) the gel content is higher than 80% by weight as described above, it is difficult to set the average polymerization degree of the b) THF-soluble phase portion to be equal to or higher than the lower limit (1000) of the range specified in the present invention. That is, the crosslinked vinyl chloride resin is obtained by copolymerizing a vinyl chloride monomer component and a crosslinkable monomer component (crosslinking agent) through emulsion polymerization as described later, and in this emulsion polymerization, these crosslinking agents are mainly consumed for the crosslinking formation of the gel fraction. Then, as the concentration of the crosslinking agent decreases, the crosslinking formation of the gel fraction is stopped, while the crosslinking agent is presumed to behave as a chain transfer agent, and a product with a lower polymerization degree than expected in the normal radical reaction of vinyl chloride monomers is generated.
[0022] The average polymerization degree of the b) THF-soluble phase portion is more preferably 1200 or more and 3000 or less. When a) the gel content is 80% by mass or less as described above, neither the mechanical strength nor the matting property of the molded product is sufficient. On the other hand, when a) the gel content exceeds 90% by mass as described above, a high matting property is exhibited, but the mechanical strength of the molded product becomes brittle.
[0023] In the crosslinked vinyl chloride resin of this embodiment, the gel component dispersed in the THF-soluble phase is obtained by polymerizing and converting the raw material monomers until the high a) gel content is reached in a crosslinked state. Therefore, the degree of swelling of the c) gel component is usually kept low, between 2.5 and 4.0, more preferably between 3.0 and 3.5. This low degree of swelling is highly useful because it creates fine irregularities on the painted surface, which greatly enhances the effect of diffusely reflecting light.
[0024] The crosslinked vinyl chloride resin of this embodiment, in which both a) gel content and b) average degree of polymerization of the THF-soluble phase exhibit high characteristic properties at specific values, can be manufactured by any method, but is usually manufactured as paste vinyl chloride by emulsion polymerization (including seed emulsion polymerization). Emulsion polymerization can be carried out by adjusting the conditions from conventionally known methods, but generally, the vinyl chloride monomer components are polymerized in emulsifier micelles using water as a medium, an emulsifier, and a water-soluble polymerization initiator, thereby generating latex of vinyl chloride resin particles in which the gel component is dispersed.
[0025] The concentration of the vinyl chloride monomer component in the aqueous medium is not particularly limited, but is usually 20 to 65% by mass, preferably 40 to 60% by mass.
[0026] There are no particular restrictions on the emulsifier, but anionic emulsifiers are preferred, such as alkylbenzene sulfonates such as sodium dodecylbenzenesulfonate; alkyl sulfates such as sodium lauryl sulfate and sodium tetradecyl sulfate; sulfosuccinates such as sodium dioctyl sulfosuccinate and sodium dihexyl sulfosuccinate; fatty acid salts such as sodium laurate and potassium semi-hardened beef tallow fatty acid; ethoxysulfate salts such as sodium polyoxyethylene lauryl ether sulfate and sodium polyoxyethylene nonylphenyl ether sulfate; alkanesulfonates; and alkyl ether phosphate ester salts, among which sodium alkylbenzenesulfonate and sodium alkyl sulfate are particularly preferred. The amount of emulsifier used is usually selected in the range of 0.5 to 1.2 parts by mass per 100 parts by mass of monomer, preferably 0.6 to 1.0 parts by mass.
[0027] In addition to anionic emulsifiers, nonionic surfactants such as polyoxyethylene nonylphenyl ether and polyoxyethylene sorbitan lauryl ester may be used in combination as appropriate. Furthermore, lipophilic auxiliary emulsifiers such as higher alcohols and sorbitan stearyl ester can be added during emulsion polymerization.
[0028] On the other hand, examples of water-soluble polymerization initiators include redox initiators that combine water-soluble peroxides such as potassium persulfate, ammonium persulfate, and hydrogen peroxide, or water-soluble azo compounds represented by 2,2'-azobisisobutyronitrile nitrile with reducing agents such as acidic sodium sulfite, ethylenediaminetetraacetate sodium complex salt of ferrous ions, ammonium sulfite, ascorbic acid, ferrous pyrophosphate, and formaldehyde sulfoxylate. Among these, the combination of hydrogen peroxide and iron(II) salt is particularly well known. The amount of water-soluble polymerization initiator used is usually selected in the range of 0.005 to 0.05 parts by mass per 100 parts by mass of monomer, preferably in the range of 0.01 to 0.03 parts by mass.
[0029] In addition, emulsion polymerization may be carried out by either adding chain transfer agents, seeds, etc., to the reactor entirely beforehand or by continuously adding them. From the viewpoint of polymerization stability, the polymerization temperature is preferably 35 to 70°C, and more preferably 40 to 65°C.
[0030] As described above, in this embodiment, emulsion polymerization of vinyl chloride monomer components proceeds in the presence of a crosslinking agent. However, in order for the resulting crosslinked vinyl chloride resin to satisfy both a) gel content and b) average degree of polymerization of the THF-soluble phase as specified by the present invention, it is usually necessary to carry out the crosslinking agent in the following reaction mode. That is, it is preferable to use a combination of a fast-reactive crosslinking agent with a high monomer reactivity ratio to vinyl chloride and a slow-reactive crosslinking agent with a low monomer reactivity ratio to vinyl chloride. Furthermore, these are carried out in the presence of the fast-reactive crosslinking agent from the initial stage of emulsion polymerization until polymerization progresses and the polymerization conversion rate of the vinyl chloride monomer components reaches a range of 65-85%. It is preferable to use this reaction in which the polymerization reaction is further advanced by adding the slow-reactive crosslinking agent in the presence of the aforementioned slow-reactive crosslinking agent. The emulsion polymerization method in this embodiment will be described in detail below.
[0031] In other words, in the above embodiment, first, a rapidly reacting crosslinking agent is selected and used as the crosslinking agent from the initial stage of emulsion polymerization to the final stage of polymerization. As a result, the crosslinking reaction proceeds actively during the polymerization of the vinyl chloride monomer, and the gel component that is insoluble in THF develops and is formed.
[0032] Here, the initial stage of polymerization refers, for example, to the period from the start of emulsion polymerization until the polymerization conversion rate of the vinyl chloride monomer component reaches 20% by mass. In other words, the crosslinking agent does not need to be added at the start of emulsion polymerization and present from the beginning of the reaction; it may be added later, when the polymerization reaction has progressed a little and the polymerization conversion rate reaches 20% by mass, and the crosslinking reaction may be started from there. In particular, the method of adding the crosslinking agent later, in the latter half of the initial stage of polymerization when the polymerization conversion rate is 10% to 20% by mass, is a particularly preferred method because it results in excellent matte finish when the resulting crosslinked vinyl chloride resin is molded.
[0033] Conversely, in this embodiment, the relative monomer reactivity ratio of the crosslinking agent to vinyl chloride was determined by performing copolymerization of vinyl chloride (100 moles) and the crosslinking agent (1 mole) under actual polymerization conditions (e.g., 45°C) and measuring the consumption rates of vinyl chloride and the crosslinking agent during the polymerization process. That is, in the above polymerization, a crosslinking agent with a consumption rate greater than that of vinyl chloride was designated as a crosslinking agent with a high monomer reactivity ratio to vinyl chloride, and conversely, a crosslinking agent with a consumption rate less than that of vinyl chloride was designated as a crosslinking agent with a low monomer reactivity ratio to vinyl chloride.
[0034] Furthermore, the relative reactivity ratio of a crosslinking agent to vinyl chloride can be compared by determining the resonance factor (Q), which indicates the resonance stability of the radicals produced by the addition of monomers, and the polarity factor (e), which is proportional to the charge of the double bond of the monomer, from literature values, and then calculating the monomer reactivity ratio (r1, r2) between vinyl chloride and the crosslinking agent. These monomer reactivity ratios (r1, r2) are calculated using the following formulas.
[0035] r1 = (Q1 / Q2)exp [-e1(e1-e2)] r² = (Q² / Q1)exp [-e²(e²-e¹)] (However, exp is a power exponent, Q1 is the resonance factor of the vinyl chloride monomer, Q2 is the resonance factor of the crosslinking agent, e1 is the polarity factor of the vinyl chloride monomer, and e2 is the polarity factor of the crosslinking agent.) As the fast-reactivity crosslinking agent having a higher monomer reactivity ratio relative to vinyl chloride as described above, it is sufficient that the monomer reactivity ratios r1 and r2 of vinyl chloride and the crosslinking agent satisfy the relationship of "r1<r2", and those satisfying the relationship of "r2 / r1" of 1.5 or more, particularly 5 or more, are preferred. The upper limit of "r2 / r1" is generally 500.
[0036] Examples of the aforementioned fast-reactivity crosslinking agent include acrylic acid or methacrylic acid esters of mono-polyalkylene glycol such as allyl methacrylate, allyl acrylate, polyethylene glycol diacrylate, ethylene glycol dimethacrylate, 1,3-propylene glycol dimethacrylate, divinylbenzene, trimethylolpropane diacrylate, trimethylolpropane triacrylate and the like, with allyl methacrylate being most preferred. These fast-reactivity crosslinking agents may be used alone or in combination of two or more kinds.
[0037] In the emulsion polymerization of the aforementioned aspect, such a fast-reactivity crosslinking agent may be added to the reaction solution at the initial stage of the polymerization initiation. If the added amount is too small, the formation of the gel fraction will be insufficient, which affects the imparting of matting properties to the obtained crosslinked vinyl chloride-based resin. On the other hand, if the amount is too large, the improvement of the crosslinking reaction will plateau. In view of the above, the blending amount of the fast-reactivity crosslinking agent is preferably 0.15 to 0.60 parts by mass, more preferably 0.25 to 0.50 parts by mass, relative to 100 parts by mass of the vinyl chloride-based monomer component.
[0038] The addition of the fast-reactivity crosslinking agent to the reaction solution is usually carried out by introducing the entire required amount at one time, but in addition, it may also be carried out by intermittent introduction divided into multiple times, continuous dropwise introduction, or the like.
[0039] As emulsion polymerization progresses in the presence of the above-mentioned crosslinking agent, the polymerization conversion rate of vinyl chloride monomer components in the reaction solution increases over time. In particular, the reactivity is high from the beginning of polymerization until more than half of the reaction is complete. On the other hand, as emulsion polymerization progresses in this way, vinyl chloride monomers are actively consumed in the reaction solution, and the amount of vinyl chloride monomers relative to the reaction site gradually decreases, and eventually the progress of polymerization approaches a plateau. When the polymerization conversion rate rises to 65-85%, preferably 70-82%, the polymerization is nearing its end, and the reaction no longer proceeds, or if it increases, it only increases slightly. If this is shown in terms of the pressure change in the polymerization tank, when emulsion polymerization starts and its reactivity becomes more active, the pressure in the polymerization tank increases. Then, from around 65% of the polymerization conversion rate, the pressure in the polymerization tank slows down, and when it reaches 70% or more, especially 80% or more, a rapid pressure drop of more than 0.1 MPa occurs from the tank pressure during the steady-state reaction.
[0040] In the reaction solution after the polymerization final stage, the average particle size of the vinyl chloride resin particles produced is generally 0.5 to 5.0 μm, and more preferably 0.7 to 3.0 μm.
[0041] In the emulsion polymerization of the above embodiment, the vinyl chloride monomer component is allowed to proceed in the presence of a fast-reactive crosslinking agent until the polymerization is complete, i.e., until the polymerization conversion rate of the vinyl chloride monomer component reaches 65-85%, preferably 70-82%. Then, the slow-reactive crosslinking agent is added to the reaction solution, and the polymerization reaction is further allowed to proceed in the presence of the slow-reactive crosslinking agent. The resulting crosslinked vinyl chloride resin has improved mechanical strength, such as tensile strength and tensile elongation, and achieves both good matte finish and high mechanical strength.
[0042] The inventors believe that the mechanical strength of the crosslinked vinyl chloride resin is improved by proceeding with the polymerization reaction in the presence of a slow-reactive crosslinking agent in this manner, due to the following mechanism. Specifically, they anticipate that the fast-reactive crosslinking agent, in emulsion polymerization, is primarily used for crosslinking the gel component in the initial stages of the reaction, while in the later stages of the reaction, as the concentration of the fast-reactive crosslinking agent decreases, it behaves like a chain transfer agent. As a result, the average degree of polymerization of the THF-soluble phase is generally only 700 to 1100, and in particular, as low as 800 to 1000.
[0043] As a result, in the generated vinyl chloride resin particles, the THF-soluble phase has a non-crosslinked or low-crosslinked structure, and this does not change significantly even when the amount of rapidly reactive crosslinking agent is increased or the emulsion polymerization reaction time is extended. From the above, it is presumed that the THF-soluble phase in vinyl chloride resin particles is fragile, and this is the reason why the mechanical strength of the crosslinked vinyl chloride resin is not sufficiently high.
[0044] In contrast, as described above, if emulsion polymerization of vinyl chloride monomer components is carried out in the presence of a fast-reactive crosslinking agent until the end of polymerization (until the polymerization conversion rate of vinyl chloride monomer components reaches a range of 65-85%), and then a slow-reactive crosslinking agent is added to the reaction solution to further proceed with the polymerization reaction, in addition to some progress of the polymerization reaction by the vinyl chloride monomers remaining in the reaction solution at the end of polymerization, crosslinking polymerization occurs by the slow-reactive crosslinking agent with a different behavior than that of the fast-reactive crosslinking agent. That is, the slow-reactive crosslinking agent does not have as strong an effect on promoting crosslinking of the gel component as the fast-reactive crosslinking agent, but on the other hand, it has an excellent effect on creating a crosslinked structure in the THF-soluble phase. Therefore, if a slow-reactive crosslinking agent is added to the reaction solution that has reached the end of polymerization and additional polymerization is carried out, the crosslinked structure of the THF-soluble phase in the resulting vinyl chloride resin particles will also be well-developed, and it is presumed that the resulting crosslinked vinyl chloride resin will have improved mechanical strength.
[0045] Furthermore, if the slow-reactive crosslinking agent is added together with the fast-reactive crosslinking agent from the early stages of polymerization, rather than at the end of polymerization, the slow-reactive crosslinking agent competes with the fast-reactive crosslinking agent for the initial crosslinking of the gel, and a certain amount of it is used for crosslinking the gel, preventing the crosslinked structure of the THF-soluble phase from developing sufficiently. Moreover, in gels that significantly contain a crosslinked structure due to the slow-reactive crosslinking agent, the crosslinked vinyl chloride resin tends to swell more, and its matte finish and mechanical strength tend to decrease.
[0046] The slow-reactive crosslinking agent should have monomer reactivity ratios r1 and r2 between vinyl chloride and the crosslinking agent such that "r1 > r2", but it is preferable that "r2 / r1" is 0.90 or less, and particularly 0.70 or less. The lower limit of "r2 / r1" is generally 0.05.
[0047] Examples of the slow-reactive crosslinking agents mentioned above include di- or trialyl compounds such as triallyl cyanurate, triallyl isocyanurate, diallyl phthalate, diallyl maleate, and diallyl succinate, with allyl methacrylate being the most preferred. These slow-reactive crosslinking agents may be used individually or in combination of two or more.
[0048] When the emulsion polymerization reaction solution reaches the final stage of polymerization, the slow-reactive crosslinking agent can be added to allow further polymerization to proceed. However, if the amount added is too small, the crosslinking reaction with respect to the THF-soluble phase will not proceed sufficiently, making it difficult to obtain the desired improvement in mechanical strength. On the other hand, if too much is added, the crosslinking with respect to the gel component will proceed excessively, in which case the mechanical strength of the resulting crosslinked vinyl chloride resin will also be difficult to improve, and the matte finish may not be fully achieved.
[0049] Furthermore, the amount of unreacted slow-reactive crosslinking agent added increases, making the process less efficient. For these reasons, the amount of slow-reactive crosslinking agent added is preferably 0.01 to 0.10 parts by mass, and more preferably 0.02 to 0.05 parts by mass, per 100 parts by mass of vinyl chloride monomer components subjected to the reaction.
[0050] While it is common practice to add the entire required amount of the slow-reactive crosslinking agent to the reaction solution at once, it may also be added intermittently in multiple stages or continuously dropwise.
[0051] The polymerization temperature in this additional polymerization is also preferably 35 to 70°C, and more preferably 40 to 65°C, from the viewpoint of polymerization stability, similar to emulsion polymerization in the presence of the rapid-reactive crosslinking agent.
[0052] In the additional polymerization described above, the polymerization conversion rate of the vinyl chloride monomer component increases. From the viewpoint of improving the mechanical strength of the vinyl chloride resin particles, it is preferable to carry out the additional polymerization until the polymerization conversion rate is at least 5% higher than the value of the polymerization conversion rate at the time the slow-reactive crosslinking agent was added to the reaction solution. In particular, it is more preferable to carry out the additional polymerization until it is 8 to 20% higher than the polymerization conversion rate at the start of the additional polymerization, but not exceeding 100%. The polymerization conversion rate at the time of completion of the additional polymerization is preferably at least 80%, and more preferably 82 to 90%.
[0053] When additional polymerization is carried out and the polymerization conversion rate of the vinyl chloride monomer component reaches the aforementioned value, the reaction can be terminated by promptly purging the vinyl chloride monomer component from the polymerization tank. At the end of the additional polymerization, the average particle size of the vinyl chloride resin particles is generally 0.5 to 5.0 μm, and more preferably 0.7 to 3.0 μm. In addition, the average particle size of the gel component dispersed in each vinyl chloride resin particle is usually maintained at approximately the value before the additional polymerization.
[0054] By the above manufacturing method, a latex in which vinyl chloride resin particles are dispersed is obtained. By drying the latex by commonly used known means, such as spray drying, the crosslinked vinyl chloride resin is recovered as a powder with the average particle size. If necessary, it may be further pulverized to break up the agglomeration that occurred during drying and obtain a powder mainly composed of primary particles.
[0055] The obtained cross-linked vinyl chloride resin can be mixed with a plasticizer and various additives as desired, specifically heat stabilizers, fillers, foaming agents, foaming accelerators, surfactants, viscosity modifiers, adhesion promoters, colorants, diluents, UV absorbers, antioxidants, reinforcing agents, and other resins, and thoroughly kneaded to a homogeneous state using a planetary mixer, kneader, roll, grinding machine, etc., to prepare a plastisol. The liquid plastisol thus obtained can then be molded by means of casting, coating, dipping, etc., and heated, melted, and solidified to obtain a molded product.
[0056] Examples of molded products include paste PVC for molding wall materials, flooring materials, automotive interior parts, electric wires, and daily necessities. The aforementioned properties, including high matte finish and excellent mechanical strength such as tensile strength and tensile elongation, make it particularly suitable for use in flooring materials. [Examples]
[0057] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0058] In the following examples and comparative examples, the physical properties were measured using the following methods.
[0059] <Monomer reactivity ratio of the crosslinking agent> Based on the resonance factor (Q), which indicates the resonance stability of the radicals formed by monomer addition, and the polarity factor (e), which is proportional to the charge of the monomer's double bond, the monomer reactivity ratio (r1, r2) of the crosslinking agent used was determined by the following formula. r1 = (Q1 / Q2)exp [-e1(e1-e2)] r² = (Q² / Q1)exp [-e²(e²-e¹)] (However, exp is a power exponent, Q1 is the resonance factor for the vinyl chloride monomer, Q2 is the resonance factor for the crosslinking agent, e1 is the polarity factor for the vinyl chloride monomer, and e2 is the polarity factor for the crosslinking agent.)
[0060] <Polymerization conversion rate of vinyl chloride monomer components> The latex obtained by emulsion polymerization was dried in an oven at 110°C to determine the solid content concentration (%) (A). The polymerization conversion rate of the vinyl chloride monomer component was then calculated using the following formula, with the mass of vinyl chloride monomers charged into the polymerization tank (B), the amount of seeds dispersed in the seed latex (solid content mass) (C), the water content of the deionized water charged into the polymerization tank, as well as the polymerization raw materials such as seed latex and emulsifiers (D), and the total mass of the pure polymerization raw materials other than vinyl chloride monomers and seed latex charged into the polymerization tank (excluding volatile raw materials) (E). Polymerization conversion rate (%) = {(A) × (D) / ((B) × (100 - (A)) - ((C) + (E)) / (B)} × 100 <Average particle size of vinyl chloride monomer particles dispersed in latex> Using a centrifugal sedimentation particle size distribution analyzer (BI-DCP, manufactured by Titan Technologies, Inc.), the D50 particle size was determined by measuring latex diluted to a concentration of 1.0 mass% at 23°C at 1500 rpm for 60 minutes.
[0061] <Gel content and degree of swelling> 2.50 g of the solid content (F) obtained by drying the latex obtained by emulsion polymerization was placed in a flask, 50 ml of THF was added, and a reflux tube was attached. The mixture was refluxed for 5 hours while stirring with a magnetic stirrer to dissolve the solid content (F). The dissolved solid content (F) obtained by reflux was added to a pre-weighed empty centrifuge tube (G), and centrifugation was performed at 18,000 rpm for 30 minutes in a high-speed refrigerated centrifuge (CR22N, rotor R18AY, manufactured by Eppendorf Hi-Mac Technologies, Inc.) cooled to 4°C. The centrifuge tube (H) after removing the supernatant was weighed, and the centrifuge tube (I) that had been dried under reduced pressure in a vacuum dryer at 40°C for 12 hours or more was weighed.
[0062] The gel content and degree of swelling were determined from the obtained results using the following formula. Gel content (mass%): {(I)-(G)} / (F)×100 Swelling degree of the gel component: {(H)-(I)} / {(I)-(G)}.
[0063] <Average degree of polymerization of THF soluble phase portion> In the aforementioned test for <gel content and swelling degree>, the supernatant obtained by centrifuging the solid content (G) solution was added dropwise to methanol collected in a beaker while stirring with a magnetic stirrer. After standing, the precipitate was re-set by suction filtration and dried at 40°C for more than 12 hours to separate the THF soluble phase. 0.25 g of this THF soluble phase was weighed and placed in a 50 ml volumetric flask, an appropriate amount of cyclohexanone was added, and then it was dissolved by immersion in a warm bath. Subsequently, cyclohexanone was added at 25°C to adjust the concentration to 0.005 g / ml to prepare the evaluation sample. For this evaluation sample, the drop time t1 was measured using an Ubbelohde viscometer. The drop time t0 of cyclohexanone was also measured. Specific viscosity η=t1 / t0 The specific viscosity was determined, and the average degree of polymerization of the THF-soluble phase was calculated from the specific viscosity-average degree of polymerization conversion table.
[0064] <Evaluation of the matte (gloss) properties of cross-linked polyvinyl chloride resins> 150 g of the aforementioned solid content (E) (cross-linked vinyl chloride resin), 90 g of dioctyl phthalate (DOP) (manufactured by J-Plus Co., Ltd.), and 3 g of Ba-Zn stabilizer (Katsuta Chemical Co., Ltd. "BZ-100CJ") were placed in a 500 ml plastic cup and kneaded at 2000 rpm for 5 minutes using a dissolver (Primix Co., Ltd. Lab-Solution, homodisperser stirring) to prepare a plastisol. This was coated onto release paper to a thickness of 200 μm, heated in a 150°C oven for 30 seconds to produce a semigel sheet, and then reheated in a 220°C oven for 60 seconds. The gloss of the obtained evaluation molded product was measured with a gloss meter (Nippon Denshoku Industries Co., Ltd. "VG8000"), and the matte finish (gloss) of the cross-linked vinyl chloride resin was used as the evaluation index.
[0065] <Evaluation of tensile strength and tensile elongation of cross-linked polyvinyl chloride resins> Molded articles for evaluation produced by the same method as in the aforementioned matte property evaluation were punched out in 5 pieces each in the direction perpendicular to the coating direction using No. 2 dumbbells, and pulled at 200 mm / min with an autograph ("AGS-X" manufactured by Shimadzu Corporation) until the sample broke, and the tensile strength and elongation were measured by the following formulas. Tensile strength (MPa) = Maximum stress (N) / Cross-sectional area of test piece (mm 2 ) Elongation (%) = {(Distance between marked lines at break) - (Distance between marked lines before test)} / (Distance between marked lines before test) × 100 Example 1 A pressure-resistant reactor equipped with a stainless steel stirrer and a jacket was charged with 90 parts of ion-exchanged water, 3.0 parts (in terms of solid content) of vinyl chloride seed latex (average particle size 0.4 μm), 0.10 parts of sodium formaldehyde sulfoxylate, and 0.001 parts of iron(III) chloride hexahydrate respectively. After degassing, 100 parts of vinyl chloride was further charged. Then, the temperature was raised to 46°C, and 0.012 parts (in terms of pure content) of a 0.03% aqueous hydrogen peroxide solution was continuously added over 12 hours to allow emulsion polymerization to proceed.
[0066] At the early stage of polymerization, when the polymerization reaction rate of vinyl chloride reached 15%, 0.30 parts of allyl methacrylate (AMA) was added, and 0.70 parts (in terms of solid content) of a 10% aqueous sodium lauryl sulfate solution was added intermittently until the reaction was completed. Here, the relationship between r2 of allyl methacrylate (AMA) and r1 of vinyl chloride satisfies the aforementioned "r1 < r2", and the aforementioned "r2 / r1" is in the range of 5 to 500, and the allyl methacrylate (AMA) belongs to the fast-reacting crosslinking agent.
[0067] The emulsion polymerization described above was continued until the polymerization conversion rate of vinyl chloride reached 75%, at which point 0.03 parts of diallyl phthalate (DAP) were added to further advance the polymerization reaction. Here, the relationship between r2 of diallyl phthalate (DAP) and r1 of vinyl chloride was r2 = 0.38 and r1 = 1.68, satisfying the relationship "r1 > r2", and furthermore, "r2 / r1" was 0.23, indicating that diallyl phthalate (DAP) belongs to the category of slow-reactive crosslinking agents.
[0068] The emulsion polymerization was continued until the polymerization conversion rate of vinyl chloride reached 85%, at which point the unreacted monomers were removed and the emulsion polymerization was terminated. In the resulting latex, the average particle size (primary particle size) of the vinyl chloride monomer particles dispersed therein was 1.0 μm, and the solid content concentration was 43% by weight. A cross-linked vinyl chloride resin was produced by spray drying this latex.
[0069] The manufacturing conditions and the properties of the obtained latex and crosslinked polyvinyl chloride resin are shown in Tables 1 and 2, respectively.
[0070] Examples 2-4 In Example 1, a cross-linked vinyl chloride resin was produced in the same manner as in Example 1, except that the timing of adding diallyl phthalate as a slow-reactive cross-linking agent after continuing emulsion polymerization was changed to the timing at which the polymerization reaction rate of vinyl chloride was reached, as shown in Table 1.
[0071] The properties of the obtained latex and crosslinked polyvinyl chloride resin are shown in Table 2, respectively.
[0072] Comparative Example 1 In Example 1, a cross-linked vinyl chloride resin was produced in the same manner as in Example 1, except that instead of adding diallyl phthalate, a slow-reactive cross-linking agent, after the emulsion polymerization had continued, it was added at the same time as the addition of allyl methacrylate, when the polymerization reaction rate of vinyl chloride reached 15%.
[0073] The properties of the obtained latex and crosslinked polyvinyl chloride resin are shown in Table 2, respectively.
[0074] Comparative Example 2 In Example 1, after continuing emulsion polymerization, no additional diallyl phthalate, a slow-reactive crosslinking agent, was added. The polymerization was allowed to proceed until the polymerization conversion rate of vinyl chloride reached 85%, and the reaction was terminated. In addition, a crosslinked vinyl chloride resin was produced in the same manner as in Example 1.
[0075] The properties of the obtained latex and crosslinked polyvinyl chloride resin are shown in Tables 1 and 2, respectively.
[0076] Comparative Example 3 In Example 1, a cross-linked vinyl chloride resin was produced in the same manner as in Example 1, except that the timing of adding diallyl phthalate as a slow-reactive cross-linking agent after continuing emulsion polymerization was set to when the polymerization conversion rate of vinyl chloride reached 63%.
[0077] The properties of the obtained latex and crosslinked polyvinyl chloride resin are shown in Tables 1 and 2, respectively.
[0078] Examples 5-6 In Example 1, a cross-linked vinyl chloride resin was produced in the same manner as in Example 1, except that the amount of allyl methacrylate added as a rapidly reactive cross-linking agent at the initial stage of polymerization was changed to the amount shown in Table 1.
[0079] The properties of the obtained latex and crosslinked polyvinyl chloride resin are shown in Table 2, respectively.
[0080] Examples 7 and 8 In Example 1, a cross-linked vinyl chloride resin was produced in the same manner as in Example 1, except that the amount of diallyl phthalate added as a slow-reactive cross-linking agent was changed to the amount shown in Table 1.
[0081] The properties of the obtained latex and crosslinked polyvinyl chloride resin are shown in Table 2, respectively.
[0082] Examples 9 and 10 A crosslinked vinyl chloride resin was produced in the same manner as in Example 1, except that the addition timing of allyl methacrylate added as a fast-reactive crosslinking agent at the initial stage of polymerization initiation in the emulsion polymerization in Example 1 was changed to the arrival timing of the polymerization conversion rate of vinyl chloride shown in Table 1.
[0083] The properties of the obtained latex and the crosslinked vinyl chloride resin are respectively shown in Table 2.
[0084] Comparative Example 4 A crosslinked vinyl chloride resin was produced in the same manner as in Example 1, except that in Example 1, the addition timing of allyl methacrylate added as a fast-reactive crosslinking agent was changed to the point after the initial stage of polymerization initiation of emulsion polymerization, when the polymerization conversion rate of vinyl chloride reached 25%.
[0085] The properties of the obtained latex and the crosslinked vinyl chloride resin are respectively shown in Table 2.
[0086] Example 11 A crosslinked vinyl chloride resin was produced in the same manner as in Example 1, except that allyl methacrylate added as a fast-reactive crosslinking agent in Example 1 was replaced with ethylene glycol dimethacrylate. Here, regarding the relationship between r2 of ethylene glycol dimethacrylate and r1 of vinyl chloride, r2 is 20, while r1 is 0.05, which satisfy the aforementioned relationship of "r1<r2", and further, the aforementioned "r2 / r1" is 400, and the ethylene glycol dimethacrylate belonged to fast-reactive crosslinking agents.
[0087] The properties of the obtained latex and the crosslinked vinyl chloride resin are respectively shown in Table 2.
[0088] Example 12 In Example 1, a crosslinked vinyl chloride-based resin was produced in the same manner as in Example 1, except that diallyl phthalate added as a slow-reactive crosslinking agent was replaced with triallyl cyanurate. Here, regarding the relationship between r2 of triallyl cyanurate and r1 of vinyl chloride, r2 was 0.14 and r1 was 1.7, which satisfied the aforementioned relationship of "r1<r2", and further, the aforementioned "r2 / r1" was 0.08, so the triallyl cyanurate belonged to the slow-reactive crosslinking agent.
[0089] The properties of the obtained latex and the crosslinked vinyl chloride-based resin are respectively shown in Table 2.
[0090] Comparative Example 5 The production of the crosslinked vinyl chloride-based resin by emulsion polymerization carried out in Example 1 was implemented instead according to fine suspension polymerization.
[0091] Specifically, a pressure-resistant reactor equipped with a stainless steel stirrer and a jacket was charged with 85 parts of ion-exchanged water, 0.70 parts (in terms of solid content) of a 10% sodium lauryl sulfate aqueous solution, and 0.05 parts of bis(2-ethylhexyl) peroxydicarbonate. After degassing, 100 parts of vinyl chloride monomer was charged. Further, 1.0 part of a lauryl alcohol / myristyl alcohol mixture and 0.05 parts of di-(2-ethylhexyl) peroxydicarbonate were charged, and after degassing under reduced pressure, 100 parts of vinyl chloride monomer was charged and mixed with stirring.
[0092] After this mixture was homogenized with a homogenizer, it was transferred to another degassed pressure-resistant reactor, the temperature was raised to 46°C to initiate fine suspension polymerization, and when the polymerization reaction rate of vinyl chloride reached 15% at the initial stage of polymerization initiation, 0.30 parts of allyl methacrylate (AMA) was added.
[0093] The above fine suspension polymerization was continued, and when the polymerization conversion rate of vinyl chloride reached 75%, 0.03 parts of diallyl phthalate (DAP) was added to further proceed the polymerization reaction.
[0094] The above fine suspension polymerization was continued until the polymerization conversion rate of vinyl chloride reached 85%, at which point the unreacted monomers were removed and the emulsion polymerization was terminated. In the resulting latex, the average particle size (primary particle size) of the vinyl chloride monomer particles dispersed therein was 1.0 μm, and the solid content concentration was 43% by weight. A cross-linked vinyl chloride resin was produced by spray drying this latex.
[0095] The manufacturing conditions and the properties of the obtained latex and cross-linked polyvinyl chloride resin are shown in Tables 1 and 2.
[0096] [Table 1]
[0097] [Table 2]
[0098] [Table 3]
[0099] [Table 4]
Claims
1. A vinyl chloride monomer component mainly containing vinyl chloride and a crosslinkable monomer component consisting of a vinyl compound that can copolymerize with it are copolymerized. a) The gel content is greater than 80% by mass and less than or equal to 90% by mass, b) The average degree of polymerization of the tetrahydrofuran soluble phase is 1000 or more and 4500 or less. A cross-linked vinyl chloride resin characterized by the following features.
2. moreover, c) The degree of swelling of the gel component is 3.0 or higher and 3.5 or lower. The crosslinked vinyl chloride resin according to claim 1.
3. The aforementioned crosslinkable monomer component is an embodiment in which a rapidly reactive crosslinking agent having a high monomer reactivity ratio with respect to vinyl chloride and a slowly reactive crosslinking agent having a low monomer reactivity ratio with respect to vinyl chloride are used in combination. A crosslinked vinyl chloride resin according to claim 1 or claim 2.
4. The crosslinked vinyl chloride resin according to claim 1 or claim 2, wherein the rapidly reactive crosslinking agent is allyl methacrylate.
5. The crosslinked vinyl chloride resin according to claim 1 or claim 2, wherein the slow-reactive crosslinking agent is diallyl phthalate.
6. A crosslinked vinyl chloride resin according to claim 1 or claim 2, comprising powder with an average particle size of 0.5 μm or more and 5.0 μm or less.
Citation Information
Patent Citations
Production of polyvinyl chloride
JP1986293203A
Manufacture of semiconductor device
JP1988058858A
Vinyl chloride paste resin
JP2009179744A